A Case Study on Graphically Modelling and Detecting Knowledge Mobility Risks - Micallef, Mark; Colombo, Christian (Electronic Communications of the EASST, 2013)
As the world continues to increasingly depend on a knowledge economy, companies are realising that their most valuable asset is knowledge held by their employees. This asset is hard to track, manage and retain especially in a situation where employees are free to job-hop for better pay after providing a few weeks’ notice to their employers. In previous work we have defined the concept of knowledge risk, and presented a graph-based approach for detecting it. In this paper, we present the results of a case study which employs knowledge graphs in the context of four software development teams.